Annual Report For 1973-74 - Texas Coll. and Univ. System, Austin. Coordinating Board; Texas Coll. and Univ. System, Austin. Coordinating Board ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
A trio of themes--economy, efficiency, and reform in higher education--dominated the work of the Coordinating Board, Texas College and University System during the year 1970-71. The whole nature of post-high school education is changing. Post-secondary education today must not only meet the needs of students seeking traditional academic and professional programs, but also the needs of those seeking vocational and occupational courses that lead directly to the world of work. The activities of the Coordinating Board during 1970-71 described in this report were directed to 5 main areas of concern: (1) expansion of the system; (2) program development; (3) financial planning and administration; (4) student services; and (5) campus planning and facilities. (Author/HS)
Educational level discussed: Higher Education.
Microfiche.
Keywords: College Students; Educational Administration; Educational Facilities; Educational Finance; Educational Planning; Financial Support; Higher Education